Tailoring Bimetallic Pt/Pd Cryogels for Efficient Ethanol Electro‐Oxidation - Hadir Borg; Dániel Zámbó; Patrick Bessel; Daniel Kranz; Marina Rosebrock; Franziska Lübkemann‐Warwas; Nadja C. Bigall; Dirk Dorfs (ChemElectroChem)
Abstract Cryogels made of colloidal nanoparticles (NPs) are a unique material class with a high specific surface area and tunable microstructure. Flash freezing of the nanoparticle building blocks and subsequent freeze‐drying of the gels, the so‐called cryoaerogelation, allows significant control over morphology, stability and improved electrocatalytic performance. In the present work, the first bimetallic Pt/Pd cryogel films of mixed Pt and Pd NPs are prepared in different molar ratios. High‐resolution microscopic and spectroscopic characterization techniques are applied to confirm the final Pt : Pd ratio besides the distribution of nanoparticles throughout the cryogel structure. Scanning electron microscopy (SEM) images of the different prepared cryogel films show a cellular to dendritic superstructure regardless of the Pt and/or Pd composition in a highly reproducible manner. Elemental analysis shows homogenous distribution of Pt and Pd NPs at the microscale for all samples. Since the prepared materials are of utmost importance for catalytic applications, their electrocatalytic activity toward ethanol oxidation reaction (EOR) is investigated. Fine‐tuning the concentration of the building blocks, the structure, thickness, and composition of the porous coatings enables high electrocatalytic activity to be achieved. Cryogel thin films with an atomic ratio of 1 : 4 Pt : Pd have the highest electrocatalytic activity for EOR.